Lung Microbiota Signature and Corticosteroid Responses in Pneumonia-Associated Acute Respiratory Distress Syndrome in Hematological Patients - Shen J; Hu Y; Lv J; Zhao H; Wang B; Yang S; Du A; Liu S; An Y (Dove Medical Press, 2022)
Jiawei Shen,1,* Yan Hu,2,* Jie Lv,1 Huiying Zhao,1 Bin Wang,1 Shuguang Yang,1 Anqi Du,1 Shuang Liu,2 Youzhong An1 1Department of Critical Care Medicine, Peking University People's Hospital, Beijing, People's Republic of China; 2Department of Respiratory and Critical Care Medicine, Peking University International Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Youzhong An, Department of Critical Care Medicine, Peking University People's Hospital, Beijing, People's Republic of China, Email bjicu_bmc@163.comObjective: In this study, we aim to classify hematological patients with the pneumonia-associated acute respiratory syndrome (ARDS) into different groups that were characterized by distinct early responsiveness to corticosteroids, describe the microbiota signatures of the non-responders and responders, and compare the prognosis of the two groups.Methods: Hematological patients with ARDS were included and treated with mechanical ventilation and corticosteroid. According to the early improvement to the corticosteroid therapy, patients were classified as non-responders and responders. The lung microbiota signatures and the outcomes of the non-responders and responders were compared.Results: Fifty patients were included in this study. Twenty-eight patients were classed as non-responders and 22 as responders. Compared to the non-responders, responders had higher serum levels of IL-6, IL-8, TNF-α and CRP, their lung microbiota was with lower alpha diversity and enriched with virus species. The responders had an overall higher ventilator free days than the non-responders [4 (0- 6) vs 6 (0- 10), p=0.034], for survivors the difference was more significant [5 (3- 6) vs 8 (3- 10), p=0.012]. Survival analysis showed that there was no difference in survival rate between the two groups over time (Log-rank p=0.073). When non-responders were stratified into subgroups of patients with infection or co-infection, those non-responders with co-infection had significantly lower survival rate than other patients (Log-rank p= 0.028).Conclusion: For hematological patients with pneumonia-associated ARDS, the responders of corticosteroids had higher ventilator free days at day 28 than the non-responders. The microbiota signatures were distinct in the two groups. The non-responders with coinfections had the lowest survival rate when compared to the non-responders with no coinfections and the responders.Keywords: microbiota, acute respiratory distress syndrome, corticosteroid, hematologic neoplasms